Resiliensi Ekologis Perempuan Penyintas KDRT dalam Konteks Pendampingan Pokja PPA Kabupaten Demak - Tabita Karen Debora; Arianti Ina Restiani Hunga; Antik Tri Susanti (PERSEPTIF: Jurnal Ilmu Sosial dan Humaniora, 2026)
Domestic violence not only affects women's lives but also requires a process of recovery and rebuilding after experiencing violence. This study aims to understand the experiences of women survivors of domestic violence in developing resilience and to identify the supporting and inhibiting factors within the context of assistance services provided by the PPA Working Group in Demak Regency. The study employed a qualitative approach with a descriptive method. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed using Michael Ungar's Ecological Resilience Theory. The findings show that resilience develops through awareness of gender injustice, the courage to leave abusive relationships, and the development of psychological and economic independence. Family support and assistance services provided by the PPA Working Group serve as important resources in the recovery process, while patriarchal culture and social stigma act as barriers. The findings emphasize that resilience among women survivors of domestic violence is not solely an individual capacity but is shaped through the interaction between individual capacities and available resources within social and institutional environments.